Pendampingan Penyusunan Dokumen Pelaporan Keuangan LAZISMU Kabupaten Kutai Timur - Anisa Kusumawardani; Abdurrahman Maulana Yusuf; Sitti Rahma Sudirman (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Zakat is one of the important pillars in Islam, which requires Muslims to give part of their wealth to those in need. Optimizing the management and reporting of zakat funds in Muhammadiyah is very important to ensure transparency, accountability, and trust from Muzakki (zakat donors) and Mustahik (zakat recipients). This Community Service Activity aims to improve understanding in the field of accounting at Lazismu Kutai Timur, East Kalimantan. The method of implementing this PKM is carried out by means of socialization, namely by delivering material on accounting regulations and techniques. Furthermore, assistance is also provided by directly assisting with problems faced by employees and staff related to accounting. The results obtained from this PKM activity are to improve employee understanding, especially in the management or administration of accounting which can ultimately improve the quality of financial reports. Furthermore, identifying obstacles and challenges faced by employees related to accounting, relevant policy recommendations will be prepared to improve the effectiveness of financial reporting training and education at Lazismu Kutai Timur. This PKM is also expected to provide a real contribution in improving financial reporting at the Lazismu unit of Kutai Timur Regency, as well as providing a better understanding of the importance of financial reporting in local economic development.